2009
DOI: 10.2340/16501977-0291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal water and adjunctive electrotherapy on chronic low back pain: A double-blind, randomized, follow-up study

Abstract: In the group treated with thermal water, improvement occurred earlier, lasted longer and was statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 26 publications
(28 reference statements)
2
28
0
8
Order By: Relevance
“…Among these, we found 18 possibly relevant studies for data retrieval according to the initial inclusion criteria (clinical trials) (Szucs et al 1989; Konrad et al 1992; Kovacs and Bender 2002; Holló et al 2004; Balogh et al 2005; Bender et al 2007; Balint et al 2007; Gaal et al 2008; Olah et al 2008; Zámbó et al 2008; Nagy et al 2009a, b; Kulisch et al 2009; Olah et al 2010, 2011; Tefner et al 2012; Horvath et al 2012; Kovacs et al 2012). Data from 1,199 subjects (patients and controls) of the 18 clinical studies were evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, we found 18 possibly relevant studies for data retrieval according to the initial inclusion criteria (clinical trials) (Szucs et al 1989; Konrad et al 1992; Kovacs and Bender 2002; Holló et al 2004; Balogh et al 2005; Bender et al 2007; Balint et al 2007; Gaal et al 2008; Olah et al 2008; Zámbó et al 2008; Nagy et al 2009a, b; Kulisch et al 2009; Olah et al 2010, 2011; Tefner et al 2012; Horvath et al 2012; Kovacs et al 2012). Data from 1,199 subjects (patients and controls) of the 18 clinical studies were evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Another Hungarian trial of a similar design but on osteoarthritis(OA) patients was the first trial to be reported in English (Szucs et al 1989); it has been followed by a series of controlled trials published by Hungarian authors in the international literature. Some of the Hungarian clinical trials are specialised in that their study populations were recruited from local, ambulatory patients, their design eliminated the placebo effect of the spa environment and atmosphere, and the control subjects were treated with heated tap water (Szucs et al 1989; Kovacs and Bender 2002; Balogh et al 2005; Bender et al 2007; Balint et al 2007; Zámbó et al 2008; Kulisch et al 2009; Olah et al 2010; Kovacs et al 2012; Tefner et al 2012). Recently, Karagülle and Karagülle (2004), as well as Katz et al (2012) reviewed Turkish and Israeli balneological trials, so to follow suit, we decided to undertake a systematic review of trials by Hungarian authors.…”
Section: Introductionmentioning
confidence: 99%
“…M. Vitale, remdamasis "PubMed" duomenimis, pastebėjo, kad daugiausia balneoterapijos poveikio tyrimų 2000-2013 metais skirta uždegi-mui ir odai, mažiausiai -nervų sistemai ir ląstelių apoptozei [3]. Naujausi gydymo balneologinėmis procedūromis tyrimai patvirtina statistiškai reikšmingą pagerėjimą sergant: a) ankilozuojančiu spondilitu [49,50]; b) fibromialgija [26,51]; c) osteoartritu [52][53][54][55][56]; d) reumatoidiniu artritu [24,25]; e) psoriaze [57,69]; f ) venų varikoze [58][59][60]; g) esant apatinės nugaros dalies skausmams [61][62][63]. Falagas ir kt.…”
Section: Balneoterapijos Klinikinio Poveikio įRodymaiunclassified
“…Po A. Kulischo randomizuoto, dvigubai aklo, kontroliuojamo tyrimo pateikta išvada: gydymo terminiu vandeniu grupėje statistiškai žymus būklės pagerėjimas atsiranda anksčiau ir trunka ilgiau; balneoterapija galėtų būti efektyvia pagrindinio gydymo priemone bei kaip priedas, sustiprinantis farmakoterapijos ir fizinės terapijos teigiamą poveikį [62]. N. Kesiktaso studijoje balneoterapijos grupėje pasiekti geresni rezultatai nugaros ekstenzinių raumenų teste (p < 0,05), modifikuotame Šobero teste (p < 0,03), "Oswestry" neįgalumo indekse ir kai kuriose SF-36 skalėse (gyvybinė energija, socialinė funkcija, vaidmens apribojime dėl fizinių problemų ir bendros sveikatos (p < 0,05) [63].…”
Section: Kaulų-raumenų Sistemaunclassified
“…Akuaterapi; hidrostatik basıncın etkisiyle ödemin gerilemesi, kaslarda gevşeme, algojenik mediatörlerin dokudan uzaklaştırılması gibi faydalar sağlamaktadır. Ayrıca suyun kaldırma kuvveti sayesinde eklemlere binen yük azalmakta, su direncine karşı yapılan egzersizler ile kas güçlenmesi sağlanabilmektedir (3)(4)(5)(6). Balneoterapi ise belirli mineral yoğunluğuna ve sıcaklığa sahip sularda egzersiz yapmaksızın beklemek suretiyle uygulanan kür banyolarıdır.…”
Section: Introductionunclassified